International Conference on the Foundations of Digital Games 2020
DOI: 10.1145/3402942.3403011
|View full text |Cite
|
Sign up to set email alerts
|

Reflection in Game-Based Learning: A Survey of Programming Games

Abstract: Reflection is a critical aspect of the learning process. However, educational games tend to focus on supporting learning concepts rather than supporting reflection. While reflection occurs in educational games, the educational game design and research community can benefit from more knowledge of how to facilitate player reflection through game design. In this paper, we examine educational programming games and analyze how reflection is currently supported. We find that current approaches prioritize accuracy ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…Prompting players to reflect on their learning and gameplay encourages them to actively think about their actions and make purposeful decisions that better align with their goals (Rogers, 2001). Written reflection prompts are often incorporated in educational game-based learning environments to encourage self-regulated learning in players (Villareale et al, 2020;Cloude et al, 2021). To date, there has been little work investigating written student reflection data as an input modality for dynamically recognizing players' in-game goals.…”
Section: Related Workmentioning
confidence: 99%
“…Prompting players to reflect on their learning and gameplay encourages them to actively think about their actions and make purposeful decisions that better align with their goals (Rogers, 2001). Written reflection prompts are often incorporated in educational game-based learning environments to encourage self-regulated learning in players (Villareale et al, 2020;Cloude et al, 2021). To date, there has been little work investigating written student reflection data as an input modality for dynamically recognizing players' in-game goals.…”
Section: Related Workmentioning
confidence: 99%
“…Figure 3 depicts the assignment of game design elements to each stage of the Experiential Learning Cycle. , and visualise students' actions to help learners reflect and examine their process to improve learning skills (Lin et al, 1999;Villareale et al, 2020). 2) On-action reflection refers to post-gameplay reflection, such as leader boards, progress information, comparative charts with previous progress, and star rating.…”
Section: Reflective Game Design (Rgd) Frameworkmentioning
confidence: 99%
“…Games provide two types of reflections: 1) In-action reflection refers to reflective feedback during gameplay in Heads-up displays (HUDs), reflective prompts, process models, audio/visual feedback, and social discourse. For instance, in CodeCombat (https://codecombat.com/), the reflective feedback is used to highlight the player's code, line by line and visualise the result of a player's code in a playback (Figure 4 (b)), and visualise students' actions to help learners reflect and examine their process to improve learning skills(Lin et al, 1999;Villareale et al, 2020). 2) On-action reflection refers to post-gameplay reflection, such as leader boards, progress information, comparative charts with previous progress, and star rating.…”
mentioning
confidence: 99%
“…Several research projects have been reported in the CS education literature that focuses on educational games for learning programming (Barnes et al, 2007;Malliarakis et al, 2014;Shabalina et al, 2008;Villareale et al, 2020). The working group for Game Development for Computer Science Education (ITiCSE-2016) examined nearly 120 games related to CS education and found more than half of the games focus on some aspect of programming (Johnson et al, 2016).…”
Section: Game-based Learning Systems (Educational Games Game Design T...mentioning
confidence: 99%